Envolvimento de receptores muscarínicos centrais no controle da ingestão de sódio - Anesio, Augusto (Universidade Federal de São Carlos, 2017)
Water and sodium intake are fundamental behaviors for body fluid homeostasis. These behaviors are controlled by a neural circuitry involving facilitatory and inhibitory mechanisms, which are modulated by signals activated by changes in body fluid volume and composition. Important inhibitory mechanisms for water intake and particularly for sodium intake are located in the lateral parabrachial nucleus (LPBN), a pontine structure. It is known that LPBN inhibitory mechanisms are controlled by several neurotransmitters, some increasing, others reducing the action of this nucleus on sodium intake...
Keywords: Apetite ao sódio; Pilocarpina; Muscimol; Moxonidina; Receptores muscarínicos; Sodium appetite; Pilocarpine; Muscimo; Moxonidine; Muscarinic receptors; CIENCIAS BIOLOGICAS::FISIOLOGIA